2007
DOI: 10.1021/jf061506p
|View full text |Cite
|
Sign up to set email alerts
|

First Application of a Microsphere-Based Immunoassay to the Detection of Genetically Modified Organisms (GMOs):  Quantification of Cry1Ab Protein in Genetically Modified Maize

Abstract: An innovative covalent microsphere immunoassay, based on the usage of fluorescent beads coupled to a specific antibody, was developed for the quantification of the endotoxin Cry1Ab present in MON810 and Bt11 genetically modified (GM) maize lines. In particular, a specific protocol was developed to assess the presence of Cry1Ab in a very broad range of GM maize concentrations, from 0.1 to 100% [weight of genetically modified organism (GMO)/weight]. Test linearity was achieved in the range of values from 0.1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…A number of researchers have performed microsphere-based assays to detect potential contaminants of foods: Dunbar et al [2] detected several bacterial pathogens in phosphate-buffered saline (PBS), Ikeda et al [3] detected pathogenic bacteria using extracted RNA, Fantozzi et al [4] detected a genetically modified maize protein, while Haasnoot and du Pre [5] demonstrated a triplex immunoassay for vegetable proteins in a milk powder matrix. Although these studies demonstrated detection of food-borne pathogens, with the exception of Haasnoot and du Pre, application of these assays to a wide range of real-world food matrices was not demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have performed microsphere-based assays to detect potential contaminants of foods: Dunbar et al [2] detected several bacterial pathogens in phosphate-buffered saline (PBS), Ikeda et al [3] detected pathogenic bacteria using extracted RNA, Fantozzi et al [4] detected a genetically modified maize protein, while Haasnoot and du Pre [5] demonstrated a triplex immunoassay for vegetable proteins in a milk powder matrix. Although these studies demonstrated detection of food-borne pathogens, with the exception of Haasnoot and du Pre, application of these assays to a wide range of real-world food matrices was not demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of the novel proteins produced by GM crops relies almost exclusively on the application of immunoassay technology (Fantozzi et al, 2007). Commercial immunoassays are available for most of the GM crops on the market today and have been used in a variety of large-scale applications, determining GM content (%GM) ensuring compliance with non-GM labeling requirements, and confirming the presence of high-value commodities.…”
Section: Methods Based On Protein: Immunoassay Technologymentioning
confidence: 99%
“…The microsphere-based technology was also applied for the detection of Cry1Ab protein in genetically modified maize with an LOD of 0.018% (weight (GMO)/ weight), and was described as the first application of a quantitative high-throughput immunoassay in GMO analysis with multiplex options by Fantozzi et al [37].…”
Section: Food Allergens and Proteinaceous Adulterantsmentioning
confidence: 99%